2017
DOI: 10.1177/0004563217699233
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex differences in serum adiponectin and its association with lipoprotein fractions

Abstract: Objective The correlation of adiponectin with cholesterol concentration of fractionated lipoproteins has not been well investigated. Methods This study included 174 subjects (79 men and 95 women) without diabetes. The medical record data were investigated retrospectively. The study subjects with adiponectin <8.3, > 8.3 but less 13.9, and ≥ 13.9 were classified into tertile groups: Groups A ( n = 59), B ( n = 58) and C ( n = 57), respectively. Results In women, age and HDL-C were higher in Group C than in Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
4
14
1
Order By: Relevance
“…Especially, HDL-C has been shown to be positively correlated with HMW adiponectin, which is considered the most biologically active form of adiponectin [60,64,65], independently of adiposity and of insulin sensitivity [61,63,64,65,67,68,69]. We also found that adiponectin was independently and positively correlated with HDL-C in 174 subjects without diabetes [70].…”
Section: Effects Of Adiponectin On Lipid Metabolismmentioning
confidence: 74%
“…Especially, HDL-C has been shown to be positively correlated with HMW adiponectin, which is considered the most biologically active form of adiponectin [60,64,65], independently of adiposity and of insulin sensitivity [61,63,64,65,67,68,69]. We also found that adiponectin was independently and positively correlated with HDL-C in 174 subjects without diabetes [70].…”
Section: Effects Of Adiponectin On Lipid Metabolismmentioning
confidence: 74%
“…RBP4 (Retinol binding protein 4) serum level positively correlates with insulin resistance as well [18]. Similarly, leptin was found to affect glucose metabolism through the modulation of glucagon secreted by α-cells of the pancreas [19] while visfatin concentration was related positively to the presence of diabetes [20] as it increased TNF followed by a TNF-mediated insulin resistance in adipocytes [21] • Lipid Disorders Adiponectin was positively and independently associated with higher HDL-C (High-density lipoprotein cholesterol) levels; which confirmed its protective role [22]. Marsche et al found that hypoadiponectinemia was associated with reduced cholesterol efflux capacity in macrophages in adults, leading to less HDL formation [23].…”
Section: Adipocytokines and Metabolic Diseasesmentioning
confidence: 83%
“…Adiponectin role is the attenuation of the excessive inflammatory response in the wall of the blood vessels of the placenta through inhibition of NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signaling (it is a protein complex that controls transcription of deoxyribonucleic acid (DNA) and cytokine production), decreasing CRP (C-reactive protein) and increasing nitric oxide [42] via activating endothelial nitric oxide synthase and inhibition of superoxide in endothelial cells [43]. Besides, adiponectin mediated the process of trophoblast invasion by modulation of MMP/TIMP (matrix metalloproteinase to tissue inhibitor of metalloproteinase) balance (this is a ratio between active extracellular [11][12][13], hyperlipidemia [22], diabetic kidney disease [30], polycystic ovary [32], ovarian cancer, gestational diabetes [39], systemic sclerosis [74], breast cancer [98], lung cancer [99], colon cancer [100], thyroid cancer [106], prostate cancer [108,109], glioblastoma [113], AIS [129], Duchene Muscular Dystrophy [132], pulmonary hypertension [149], obstructive sleep apnea [151], atherosclerosis [11], hypertension [158], preeclampsia [41][42][43][44], COVID-19 [164] Cervical & endometrial cancer [37,38], joint inflammation [64], bone erosion in rheumatoid arthritis [65], SLE with renal involvement [87] Adipsin Systemic sclerosis with PAH [83], SLE with renal involvement [ Insulin resistance &diabetes [11,…”
Section: • Preeclampsiamentioning
confidence: 99%
“…Maternal adiponectin has been inversely related with BMI [ 45 ], GA and positively associated with maternal age [ 46 , 47 ]. The ANN adiponectin model derived from this study was able to predict these associations too.…”
Section: Discussionmentioning
confidence: 99%